Preparing for post-discharge care of premature infants: Experiences of parents - Sandra Patricia Osorio Galeano; Sandra Catalina Ochoa Marín; Sonia Semenic (Universidad de Antioquia, 2017)
Objective. The study sought to describe the experiences of parents of premature children regarding discharge from the neonatal unit. Methodology. This was a qualitative study, in which 10 semi-structured interviews were conducted with parents of premature infants upon discharge from the neonatal unit. Data were analyzed following principles of grounded theory; open and axial coding was performed. Results. The following categories emerged from the analysis of the information: feelings experienced upon discharge, and experience of the discharge as a process; the latter category clearly identified barriers and facilitators. The results highlight that the parents experience ambivalent feelings; joy is mixed with the fear of caring for a premature child at home. Conclusion. For parents, discharge of premature children from the neonatal unit is a complex process during which conflicting feelings are experienced. Nursing must develop strategies to involve parents early in the care of their children during the hospital stay.   How to cite this article: Osorio SP, Ochoa Marín SC, Semenic S. Preparing for post-discharge care of premature infants: Experiences of parents. Invest. Educ. Enferm. 2017; 35(1):